Child Participation: A Forgotten ‘P’ Under the Ethiopian Legal System? - Alamaw, Yitagesu Muluneh (Bahir Dar University Journal of Law, 2022)
The Federal Democratic Republic of Ethiopia’s 1995 Constitutionhas been praised for its long and relatively comprehensive list ofhuman rights, providing for the rights of the child under Article 36.However, it has not categorically specified the principles underlyingthese rights, which are enshrined in the United Nations Convention onthe Rights of the Child, 1989 (CRC), and the African Charter on theRights and Well-being of the Child, 1991 (ACRWC). Thus it is logicalto question the constitutional placement of these principles. This articleanalyzes one of the basic principles upon which the rights of the childare established, i.e., participation. The author attempts to evaluate theplace of children’s right to participation within the hierarchy of theConstitution and the legal system it establishes.Although the Constitution does not explicitly provide for participationas one of the principles underlying the rights of the child in the CRCand the ACRWC, Ethiopian legislation as well as practice in the legalsystem affords opportunities in which children’s right to participate maybe implemented. Thus, the author recommends that the Constitution beread critically where the rights of the child are concerned, and furtherrecommend the strengthening of practices that recognize children’sright to participation and the creation of more space to accommodate itproperly, as there are limitations at present in these areas. Finally, thethe author advocates proper utilization of the rule of interpretationprovided under the Constitution, as this rule has great significance inthe realization of the right to child participation and general protectionof this right.